DETERMINANTS OF RELIGIOUS MODERATION AMONG UNIVERSITY STUDENTS IN INDONESIA - Raden Ahmad Muhajir Ansori; Bambang Budi Wiyono; Sultoni Sultoni; Ahmad Yusuf Sobri (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
This study examines the factors influencing religious moderation among university students and explores the role of life stress in shaping these relationships. Despite growing attention to religious moderation in higher education, limited research has systematically addressed how individual, instructional, and contextual factors interact in this process. Data were collected using a quantitative approach with an explanatory research design. The study involved university students selected through a structured sampling technique, and the data were analyzed using inferential statistical methods. The findings reveal that lecturer professionalism, student management, religiosity, religious understanding, and tolerance are positively associated with students’ religious moderation. In contrast, anti-radicalism shows a negative relationship with religious moderation. Further analysis indicates that life stress does not function as a significant moderating variable overall, although it slightly alters the strength of certain relationships, particularly by weakening the influence of religiosity while strengthening the effects of tolerance and anti-radicalism. This study contributes to the literature by highlighting the importance of integrating pedagogical practices, student development, and socio-psychological factors in fostering religious moderation.